2011
DOI: 10.1002/fam.1112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon fibre orientation on reaction‐to‐fire properties of polymer matrix composites

Abstract: SUMMARY The influence of the orientation of carbon fibres on the reaction‐to‐fire characteristics of a layered composite has been investigated in detail. 8552/IM7 prepregs were laid up to give unidirectional and quasi‐isotropic laminates. Specimen thickness (0.25 to 8.0 mm) and heat flux (15 to 80 kW/m2) were varied for irradiation. Fundamental reaction‐to‐fire properties of this composite are interpreted on the basis of the matrix components: epoxy resin and polyethersulfone. Cone calorimetry and temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 23 publications
4
49
1
Order By: Relevance
“…In fact, non‐combustible fibres such as glass and carbon fibres show a diluting effect and have influence on the velocity of combustion. Furthermore, they act as barriers in the combustion mechanism . Other authors have reported similar results.…”
Section: Resultssupporting
confidence: 63%
“…In fact, non‐combustible fibres such as glass and carbon fibres show a diluting effect and have influence on the velocity of combustion. Furthermore, they act as barriers in the combustion mechanism . Other authors have reported similar results.…”
Section: Resultssupporting
confidence: 63%
“…Nine hundred sixty prepreg layers were stacked to create a cube with dimensions shown in Figure , which was cured in an autoclave according to the manufacturers' recommended conditions . Because of the unidirectional layup of the prepreg plies, no distinguishable fiber layers exist after curing, as carbon fibers become nearly homogeneously distributed throughout the cube . Five‐millimeter thick panels were cut from the cube in various out‐of‐plane directions using a water‐cooled diamond wire saw, creating fiber angles between 0° and 15° with respect to the panel surface.…”
Section: Methodsmentioning
confidence: 99%
“…They must account for temperature‐dependent thermal properties, internal chemical reactions, material delaminations, and formation of pyrolysis products . Previous work has investigated the effects of in‐plane fiber orientation on reaction‐to‐fire properties, such as unidirectional and quasi‐isotropic, its stacking pattern, and chopped and woven fiber reinforcement . However, minimal research into the effects and applications of out‐of‐plane fiber angles has been conducted to date and is, therefore, the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Resultant char and resin‐depleted fiber plies retard the transport processes necessary for combustion. An intensive final HRR peak occurs when the migration of the pyrolysis zone reaches the panel back side and is predominantly explained by an accumulation of heat, due to the back side insulation …”
Section: Resultsmentioning
confidence: 99%